Psychedelic mysticism transforming consciousness, religious experiences, and voluntary peasants in postwar America - Shipley, Morgan (Lexington Books, 2015)
Although commonly celebrated as a distinct manifestation of Americana, hippies and psychedelics are routinely de-emphasized in favor of direct political activism, a phenomenon that constrains the full telling of the hippie counterculture as it relates to a radical religiosity defined by mutuality and altruism. Psychedelic Mysticism reevaluates the religious significance of the 1960s psychedelic counterculture, tracing how psychedelics became entheogenic, leading sixties figures to transition personal moments of enlightenment into everyday projects of social justice